Analisis Normatif-Empiris Pertimbangan Hakim dalam Tindak Pidana Ketenagakerjaan (Studi Putusan Nomor 725/Pid.Sus/2019/PN Tjk) - Bambang Hartono; Ade Darusalam (Universitas Medan Area, 2026)
This study examines the enforcement of criminal law in the field of employment, particularly violations of minimum wage regulations, through a case study of the Decision of the Tanjung Karang District Court Number 725/Pid.Sus/2019/PN Tjk. The research focuses on the factors causing the Director of PT Pratama Prima Sentosa to pay wages below the Bandar Lampung City Minimum Wage and on the legal considerations underlying the judges’ criminal verdict. The research employs a normative–empirical legal method by analyzing relevant legal provisions, including labor law, criminal procedure law, and wage regulations, and by examining their implementation through field data obtained from interviews with labor inspectors, public prosecutors, and judges. The findings indicate that the criminal offense resulted from a combination of factors, namely low compliance with mandatory minimum wage norms, deviant and recurring internal wage policies, unequal employment relations that weaken workers’ bargaining positions, and ineffective administrative supervision. From a judicial perspective, the decision was based on the negative statutory proof system through the application of Article 90 paragraph (1) in conjunction with Article 185 paragraph (1) of the Manpower Law and evidentiary standards under Article 184 paragraph (1) of the Criminal Procedure Code. The court imposed a prison sentence with probation and a fine by balancing juridical, philosophical, and sociological considerations to ensure the protection of workers’ normative rights while maintaining general deterrence.